2022
DOI: 10.24191/e-aj.v11i2.20446
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Role of Demographic Factors and University Students’ Level of Nomophobia

Abstract: The popularity of smartphones among university students is associated with the numerous features and functionalities they provide. A smartphone is the best example in this study since it is a much close gadget to people. It is an essential part to be tackled by everyone to sustain a better and more harmonious interaction among students especially. As a consequence, nomophobia is one of the symptoms of a bad disease that is happening around the world since technology has become a vital thing in our daily life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…11 In another study, Husniesham et al, observed no significant difference in the level of nomophobia across gender among study participants. 12 In meta-analysis study on nomophobia among Turkish people revealed that females had higher mean nomophobia scale scores than males. 13 Nomophobia is also linked to the fear of being unable to communicate, losing one's connection, feeling lonely, and losing one's comfort.…”
mentioning
confidence: 99%
“…11 In another study, Husniesham et al, observed no significant difference in the level of nomophobia across gender among study participants. 12 In meta-analysis study on nomophobia among Turkish people revealed that females had higher mean nomophobia scale scores than males. 13 Nomophobia is also linked to the fear of being unable to communicate, losing one's connection, feeling lonely, and losing one's comfort.…”
mentioning
confidence: 99%